Hardware improvement of FDM 3D printer: issue of bed leveling failures - Arief, Rudi Kurniawan; Adesta, Erry Yulian Triblas; Hilmy, Irfan (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Rapid Prototyping is one of many technologies that trigger the Industrial Revolution 4.0. The open source system that applied to 3D printer system make the research development grow rapidly. Most favorable research topics are in the area of extrusion head, material and functional modification. But the difficulties in leveling the heated bed has created worst user experiment and cause some catastrophic failures to be happens. This paper reviewed the research conducted around improvement of the FDM printer’s hardware. The cause of most occur failures in FDM printing also discussed. To overcome the disturbing failure caused by the lack of levelness of the heated bed, a pine trees liked pin system is introduced.